Risk factors for early viral infections after liver transplantation - Busch, Cornelius; Siegler, Benedikt Hermann; Werle, Heike; Lichtenstern, Christoph; Bruckner, Thomas; Heininger, Alexandra; Mehrabi, Arianeb; Weiss, Karl Heinz; Weigand, Markus A.; Hochreiter, Marcel (Langenbeck's archives of surgery, 2018)
Purpose: Viral infections represent a serious threat for patients after liver transplantation (LT). The identification of risk factorsduring the early post-transplant period might help to improve prevention of viral infections after LT. Methods: Between 2004 and 2010, 530 adult patients underwent LTat a large university hospital serving a metropolitan region inEurope. This retrospective single-centre study analysed putative risk factors for early viral infections with herpes simplex virus-1(HSV-1), varicella-zoster virus (VZV), Epstein-Barr virus (EBV), hepatitis A/B/C (HAV/HBV/HCV) and cytomegalovirus(CMV) in the first 3 months after LT. Results: The final analysis included 501 patients of whom 126 (25.1%) had documented viral infections after LT. No significantdifferences could be detected between patients with or without viral infections concerning 30- and 90-day mortality. Risk factorsin the early post-transplant period identified by multivariate analysis included female gender (CMV, HSV-1), the post-operativeneed for continuous veno-venous hemofiltration (CMV), septic shock (CMV), detection of fungi (CMV) and the intraoperativeamount of transfused blood (EBV). Conclusions: Enhanced vigilance regarding opportunistic infections is crucial in the management of this high-risk population ofimmunocompromised patients. In particular, attention should be paid to avoidable conditions that increase the risk of renalreplacement therapies in the post-LT setting, especially among women.Trial registration: DRKS00010672 on German Clinical Trial Register
Gesehen am 04.02.2020